1989
DOI: 10.1300/j010v14n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Discharges for Medical and Surgical Patients in an Acute Care Hospital

Abstract: A study of social work-coordinated discharges from medical and surgical units at a 387-bed tertiary care hospital in Seattle, Washington examines social, medical and organizational factors associated with overstays. Social and medical variables included an absence of social supports, multiple diagnoses, and patient/family decision-making problems. Though organizational factors within and outside the hospital were identified, the most frequent systems delay was due to lack of post-hospital beds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
1
5
1
Order By: Relevance
“…Our findings agree with Haddock (1991) and Semke et al (1989), who examined reasons for hospital overstay days and concluded that nursing homes need more information about patients, especially high needs patients, earlier in the process in order to review, for example, staffing levels for the coming weeks and availability of needed medical supplies. Although use of the fax procedure both reduced the need for telephone exchanges and increased predictability, it also required the discharge planner to take more time in obtaining consents and assembling and transmitting material.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings agree with Haddock (1991) and Semke et al (1989), who examined reasons for hospital overstay days and concluded that nursing homes need more information about patients, especially high needs patients, earlier in the process in order to review, for example, staffing levels for the coming weeks and availability of needed medical supplies. Although use of the fax procedure both reduced the need for telephone exchanges and increased predictability, it also required the discharge planner to take more time in obtaining consents and assembling and transmitting material.…”
Section: Discussionsupporting
confidence: 90%
“…Since the onset of diagnosis-related groups (DRGs), much research has been devoted to examining the effect of the prospective payment system on such factors as length of hospital stay, health status at discharge, and quality of care (e.g., Edwards, Reiley, Morris, & Doody, 1991;Langer, Drinka, & Voeks, 1991;Naylor, 1990;Sager, Leventhal, & Easterling, 1987;Semke, VanDerWeele, & Weatherley, 1989). While the impact of DRGs and, consequently, discharge planning, have become focal points of research, little attention has been directed to the transfer of patient information, which is, of course, a vital link in maintaining continuity of care across health care settings.…”
mentioning
confidence: 99%
“…Nonmedical factors identified in this group are similar to those described in previous studies, particularly family and patient decision-making and post-hospital placement and care needs. 5,7 Although this pilot study was limited to a single-site population, it is to our knowledge the first study to describe these factors in a homebound population, and may be able to guide future research and discussion on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Similar methodology and terminology have been used in previous studies examining the contribution of nonmedical factors to LOS. 5,7 While literature in other fields, such as social work, often characterize similar factors as ''social'' or ''social care'' factors, we use the term ''nonmedical'' to draw the distinction between factors that acutely reflect a patient's state of health and necessitate days spent in the hospital (eg, surgery, infection), in contrast to factors that are not direct contributors to the patient's current medical status (eg, post-hospital placement). Factors contributing to nonmedical days were determined based on previous studies and categorized as follows: nursing facility bed availability, nursing facility rejection of the patient, complications with insurance coverage, lack of patient/family agreement with discharge plan, home care service delays, and other.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation